Outcomes associated with concordance of oral antidiabetic drug treatments to prescribing information in patients with type 2 diabetes mellitus and chronic kidney disease. (May 2013) - Chen, S.Y.; Lee, Y.C.; Alas, V.; Greene, M.; Brixner, D.
Abstract Objectives: This retrospective study aims to examine the association between prescribing information (PI)-concordant oral antidiabetic drug (OAD) treatment and clinical and economic outcomes in patients with type 2 diabetes mellitus and stages 3–5 chronic kidney disease (CKD). Methods: The study used a large, national administrative claims database with laboratory findings to identify patients with a diagnosis of diabetes and indication of stages 3–5 CKD (first observed indication as the index date) between 1/1/2005 and 30/06/2009. OADs prescribed during 6 months following the index date (baseline period) were evaluated and patients were considered non-PI-concordant if any did not meet the recommendations regarding patients with renal impairment. Glycemic control and measures of healthcare costs (standardized to 2010 US dollars using the Consumer Price Index) and resource utilization were assessed during the 12 months following the baseline period. Severe hypoglycemic events were assessed after the baseline period until lost to follow-up. Regression analyses were performed after adjusting for demographic and clinical characteristics. Results: Among the 3300 patients included in the study, 2454 (74.4%) were non-PI-concordant. The non-PI-concordant patients had higher risk of severe hypoglycemic events identified in all settings (HR = 1.35, 95% CI: 1.10–1.67) and events identified in inpatient hospital setting (HR = 2.51, 95% CI: 1.49–4.22), were more likely to have inpatient hospital admissions (OR = 1.27, 95% CI: 1.02–1.57), and were less likely to have glycemic control (OR = 0.56, 95% CI: 0.44–0.71). Annual diabetes-related cost was $1638 higher in the non-PI-concordant cohort (p = 0.0048). Limitation: The retrospective cohort design does not allow for conclusions to be drawn on the causal effect of PI-concordant use based on the associations observed. Conclusion: Our findings suggest PI-concordant treatment to be associated with better clinical and diabetes-associated economic outcomes. Future research is warranted to confirm the associations found in this study.